Caleol: modificações estruturais, estereoquímica absoluta e atividade antimicrobiana dos derivados - Pedroso, Marcelo (2011)
The essential oil of the leaves of Calea clematidea, a plant of Asteraceae family used in the folk medicine in treatment of flu, stomachic disease and gastric ulcer, was extracted and of it was isolated the monoterpene caleol. This metabolite was submitted to structural modification reactions by the opening of its epoxide functional group. In the reactions catalyzed by anhydrous iron (III) chloride, the epoxide opening was selective when primary alcohols was used like nucleophile, giving like product the less substituted alcohol. In addition, the absolute stereochemistry of caleol was analyzed by NMR, where was verified that the carbon C4 configuration is R. The essential oil, the caleol and the obtained derivatives were submitted to a microbiological activity. The caleol showed best activity against bacteria and derivatives against yes.